Characterization method and application of interfacial compatibility of EPDM / phenolic aldehyde scouring-resistant thermal insulation material

The interface compatibility of EPDM/phenolone resistant insulation materials was characterized by resistance method, which solved the problem of poor interface bonding performance of the material and achieved a fast and reliable interface compatibility evaluation.

CN119492785APending Publication Date: 2025-02-21HUBEI SANJIANG AEROSPACE JIANGHE CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771464.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The interface bonding performance of EPDM/phenolene is poor insulating material, which affects the actual application of the material.

Method used

The resistance method was used to characterize the interface compatibility of the material. The carbon fiber braid was soaked in the ethylene propane/phenol mixed glue solution, and the resistance value change rate was recorded, and the interface compatibility was evaluated.

Benefits of technology

This method can quickly and easily evaluate the interface compatibility of the material, with reliable results, strong operability, and no damage to the sample.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, and particularly discloses a characterization method and application of interfacial compatibility of an ethylene-propylene-diene monomer / phenolic aldehyde scouring-resistant thermal insulation material.The characterization method comprises the following steps that S1, ethylene-propylene-diene monomer is dissolved with a solvent, phenolic resin is added, the mixture is mixed to be uniform, and an ethylene-propylene-diene monomer / phenolic aldehyde mixed glue solution is obtained; s2, connecting the two ends of a carbon fiber braided fabric to a resistance meter through wires to form a loop, then placing the carbon fiber braided fabric in a container, and adding the glue solution prepared in the step S1 into the container, so that the carbon fiber braided fabric is immersed in the glue solution except the wiring part; and S3, after the glue solution is poured, starting to record the resistance value reading at regular time, calculating the resistance change rate, and when the resistance change rate reaches the maximum moment, recording the maximum moment as Tmax, and the smaller the Tmax is, the better the interfacial compatibility is. According to the method, the sample cannot be damaged, and real-time monitoring can be realized; in-situ detection can be realized, the test process is convenient and rapid, the result is reliable, the cost is low, and the method has significant advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid rocket engine insulation materials, and in particular to a method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant insulation materials and applications thereof. Background Art

[0002] Insulation material is one of the key components of solid rocket engines. In order to ensure the normal operation of solid rocket engines under extreme conditions such as high temperature and high particle flow generated by propellant combustion, insulation materials must have excellent ablation resistance and erosion resistance. EPDM rubber insulation materials are widely used in the aerospace field due to their unique advantages. Among them, carbon fiber reinforced EPDM and phenolic resin composite materials have excellent erosion resistance, which is very suitable for the needs of solid rocket engines in increasingly harsh working environments.

[0003] Carbon fiber reinforced EPDM and phenolic resin composites are usually prepared by solution immersion method. However, an inherent problem of EPDM / phenolic erosion-resistant insulation materials is poor interfacial bonding performance, which greatly affects practical applications. Due to the poor polarity of EPDM and the low interfacial compatibility with the carbon fiber surface, it is difficult for the two to form a tight composite, which will have a certain impact on the interfacial performance of the insulation material. At present, there are two main types of improvements in the interfacial compatibility of EPDM / phenolic erosion-resistant insulation materials: phenolic resin modification and carbon fiber surface modification. Phenolic resin modification mainly uses the introduction of polar and non-polar small molecules on the macromolecular chain during the synthesis process as a bridge connecting EPDM and carbon fiber surfaces. Carbon fiber surface modification mainly uses non-polar sizing agents to change the surface properties, so as to achieve the purpose of close bonding with EPDM. Therefore, in the development of EPDM / phenolic erosion-resistant insulation materials, a reasonable and effective means is needed to characterize the interfacial compatibility of materials.

[0004] Methods for characterizing interface compatibility include electron microscopy analysis, interface shear strength test, and wettability test. The results of electron microscopy analysis are highly accurate, but the test time is long and the test cost is high. The object of the interface shear strength test is usually a carbon fiber monofilament, the sample preparation is difficult, the results are highly discrete, and it is difficult to characterize the overall performance. The wettability test requires the sample surface to be flat, which is obviously not applicable to carbon fiber braids. Summary of the invention

[0005] The invention provides a method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials and an application thereof, which can be tested simultaneously during the preparation process of the thermal insulation materials, has strong operability and high result reliability.

[0006] The technical solution of the present invention is to provide a method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials, comprising the following steps: S1, dissolving EPDM rubber with a solvent, adding phenolic resin and mixing well to prepare EPDM / phenolic mixed glue; S2, connecting the two ends of the carbon fiber braid to an ohmmeter with wires to form a loop, then placing the carbon fiber braid in a container, and adding the glue prepared in S1 to the container, so that the carbon fiber braid except the wiring part is immersed in the glue; S3, after pouring the glue, start to record the resistance value reading regularly, the initial resistance value is R0, and the later resistance value is recorded as R i (i=1,2,…,), calculate the resistance change rate X, X=R0 / R i ×100%; the moment when X reaches the maximum is recorded as T max , T max The smaller it is, the better the interface compatibility is.

[0007] Optionally, the EPDM rubber in S1 contains, in addition to the EPDM base rubber, one or more of a vulcanizer, a vulcanization accelerator, an antioxidant, a flame retardant and a plasticizer.

[0008] Optionally, the solvent is one or more of toluene, xylene, cyclohexane, heptane, gasoline, acetone, ethyl acetate, anhydrous ethanol, anhydrous methanol, and ethylene glycol.

[0009] Optionally, the phenolic resin is one or more of an ammonia-modified phenolic resin, a sodium-modified phenolic resin, a boron-modified phenolic resin and a barium-modified phenolic resin.

[0010] Optionally, when the phenolic resin is mixed, the temperature is 0-60° C., the rotation speed is 500-1000 rpm, and the stirring time is 10-60 min.

[0011] Optionally, the mass fraction of the EPDM / phenolic resin mixed glue solution is 10-50%; the mass ratio of the EPDM glue to the phenolic resin is 0.5-2:1.

[0012] Optionally, the length of the container is smaller than the length of the carbon fiber braid, and the width and depth are respectively larger than the width and thickness of the carbon fiber braid; the material of the container is one or more of polytetrafluoroethylene, polyvinyl chloride, polymethyl methacrylate and polypropylene; the accuracy of the resistance meter is milliohm level or above.

[0013] Optionally, the resistance value reading is recorded every 30 seconds during the test in S3.

[0014] Optionally, T max When ≤5min, the interface compatibility is excellent; 5<T max When ≤10min, the interface compatibility is good; 10<T max When ≤15min, the interface compatibility is medium; 15<Tmax When ≤20min, the interface compatibility is poor; T max When the time is greater than 20 min, the interfacial compatibility is extremely poor.

[0015] The present invention also relates to the application of the characterization method in the research and development of EPDM / phenolic erosion-resistant thermal insulation materials and production quality control.

[0016] The present invention has the following beneficial effects: The present invention uses the resistance method to indirectly characterize the interfacial compatibility of EPDM / phenolic erosion-resistant thermal insulation materials. Carbon fiber fabrics have a certain conductivity. During the soaking process in the EPDM / phenolic mixed glue solution, the glue components that infiltrate the fiber surface and the interior will cause the overall resistance of the carbon fiber fabric to increase. When the soaking process reaches dynamic equilibrium, the resistance value of the carbon fiber fabric no longer changes, the resistance change rate X reaches the maximum, and the soaking reaches equilibrium. The present invention uses the soaking equilibrium time T max The compatibility of the interface can be evaluated, and the wetting equilibrium time T max The smaller it is, the better the interface compatibility is.

[0017] The present invention ingeniously uses resistance change to indirectly characterize the immersion preparation process of EPDM / phenolic erosion-resistant insulation material. On the one hand, the destructiveness to the sample is almost zero, and on the other hand, the immersion process can be monitored in real time. In addition, the present invention can realize in-situ detection, the test process is convenient and rapid, the result is highly reliable, the operability is strong, the test cost is low, and it has significant advantages. DETAILED DESCRIPTION

[0018] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0019] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.

[0020] The present invention provides a method for characterizing the interfacial compatibility of EPDM / phenolic erosion-resistant thermal insulation materials, comprising the following steps: S1, dissolving EPDM rubber with a solvent, adding phenolic resin and mixing well to prepare EPDM / phenolic mixed glue; S2, connecting the two ends of the carbon fiber braid to an ohmmeter with wires to form a loop, then placing the carbon fiber braid in a container, and adding the glue prepared in S1 to the container, so that the carbon fiber braid except the wiring part is immersed in the glue; S3, after pouring the glue, start to record the resistance value reading regularly, the initial resistance value is R0, and the later resistance value is recorded as R i (i=1,2,…,), calculate the resistance change rate X, X=R0 / R i ×100%; the moment when X reaches the maximum is recorded as T max , T max The smaller it is, the better the interface compatibility is.

[0021] The EPDM / phenolic mixed adhesive contains, in addition to EPDM adhesive and phenolic resin, vulcanizers, vulcanization accelerators, antioxidants, flame retardants and plasticizers as needed.

[0022] In some embodiments, the solvent is one or more of toluene, xylene, cyclohexane, heptane, gasoline, acetone, ethyl acetate, anhydrous ethanol, anhydrous methanol, and ethylene glycol.

[0023] In some embodiments, the phenolic resin is one or more of an ammonia-modified phenolic resin, a sodium-modified phenolic resin, a boron-modified phenolic resin, and a barium-modified phenolic resin.

[0024] In some embodiments, when the phenolic resin is mixed, the temperature is 0-60° C., the rotation speed is 500-1000 rpm, and the stirring time is 10-60 min.

[0025] In the EPDM / phenolic resin mixed glue solution prepared by the present invention, the mass fraction of EPDM / phenolic resin is 10-50%, and the mass ratio of EPDM glue to phenolic resin is 0.5-2:1.

[0026] In some embodiments, the length of the container is less than the length of the carbon fiber braid, and the width and depth are respectively greater than the width and thickness of the carbon fiber braid; wherein the size of the carbon fiber braid is preferably: 12~20cm long, 2~3cm wide, and 0.4~1.0cm thick. The container is preferably a rectangular parallelepiped, and the dimensions of the internal cavity of the container in the following embodiments are 8cm long, 4cm wide, and 2cm deep; the container can also be provided with a cover. The dimensions of the cover are: 9cm long, 5cm wide, and 0.5cm high. During the immersion treatment, the EPDM / phenolic mixed glue is completely filled into the rectangular cavity. By setting a cover, the test results are reduced due to solvent volatilization during the test. After the carbon fiber fabric is cut, it is gently shaken to clean it to reduce the influence of carbon fiber debris on the glue.

[0027] The material of the container is one or more of polytetrafluoroethylene, polyvinyl chloride, polymethyl methacrylate and polypropylene; the accuracy of the resistance meter is milliohm level or above.

[0028] In the following embodiments, the resistance readings are recorded every 30 seconds in the test in S3 for a total of 20 minutes. The moment when the resistance change rate X reaches the maximum is the infiltration equilibrium time, recorded as Tmax Specific interface compatibility levels are shown in Table 1.

[0029] Table 1

[0030] Example 1 The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention comprises the following steps: (1) Dissolve 100 g of EPDM rubber in 800 g of xylene to obtain EPDM glue solution, then add 100 g of ammonia-modified phenolic resin and stir thoroughly at a stirring temperature of 25 °C, a rotation speed of 600 rpm, and a stirring time of 30 min to obtain an EPDM / phenolic mixed glue solution with a mass fraction of 20%; (2) The carbon fiber braid is made into a strip with a length of 12 cm, a width of 2 cm, and a thickness of 0.5 cm. Conductive copper sheets are pasted at both ends along the length direction and connected to a high-precision multimeter. (3) Place the carbon fiber braid in step (2) in the center of the groove of the polytetrafluoroethylene rectangle, with both ends of the carbon fiber braid extending out of the groove, and fix it with tape; (4) Pour the EPDM / phenolic adhesive mixture obtained in step (1) into the groove, cover it immediately after it is full, and start recording the resistance value readings every 30 seconds for a total of 20 minutes, and calculate the resistance change rate X and T max .

[0031] Example 1 obtained T max The time of the reaction is 4 minutes. According to the interface compatibility rating table in Table 1, ammonia-modified phenolic resin and a 20% EPDM / phenolic mixed adhesive solution with a ratio of 1:1 of EPDM / phenolic are used to prepare EPDM / phenolic erosion-resistant thermal insulation material, and the interface compatibility grade is excellent.

[0032] Example 2 The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention comprises the following steps: (1) Dissolve 50 g of EPDM rubber in 600 g of xylene to obtain EPDM glue solution, then add 100 g of ammonia-modified phenolic resin and stir thoroughly at a stirring temperature of 25 °C, a rotation speed of 600 rpm, and a stirring time of 30 min to obtain an EPDM / phenolic mixed glue solution with a mass fraction of 20%; (2) The carbon fiber braid is made into a strip with a length of 12 cm, a width of 2 cm, and a thickness of 0.5 cm. Conductive copper sheets are pasted at both ends along the length direction and connected to a high-precision multimeter. (3) The carbon fiber braid in step (2) is placed in the center of the groove of the special polytetrafluoroethylene rectangular parallelepiped, with both ends of the carbon fiber braid extending out of the groove, and fixed with tape; (4) Pour the EPDM / phenolic adhesive mixture obtained in step (1) into the groove, cover it immediately after it is full, and start recording the resistance value readings every 30 seconds for a total of 20 minutes, and calculate the resistance change rate X and T max .

[0033] Example 2 obtained T max 2min, according to the interface compatibility rating table in Table 1, ammonia-modified phenolic resin is selected, and the mass fraction of EPDM / phenolic mixed glue with a ratio of 0.5:1 is used to prepare EPDM / phenolic erosion-resistant insulation material, and the interface compatibility rating is excellent. Compared with Example 1, Example 2 reduces the ratio of EPDM, T max Reduced, showing better interface compatibility.

[0034] Example 3 The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention comprises the following steps: (1) Dissolve 100 g of EPDM rubber in 600 g of xylene to obtain EPDM glue solution, then add 50 g of ammonia-modified phenolic resin and stir thoroughly at a stirring temperature of 25 °C, a rotation speed of 600 rpm, and a stirring time of 30 min to obtain an EPDM / phenolic mixed glue solution with a mass fraction of 20%; (2) The carbon fiber braid is made into a strip with a length of 12 cm, a width of 2 cm, and a thickness of 0.5 cm. Conductive copper sheets are pasted at both ends along the length direction and connected to a high-precision multimeter. (3) The carbon fiber braid in step (2) is placed in the center of the groove of the special polytetrafluoroethylene rectangular parallelepiped, with both ends of the carbon fiber braid extending out of the groove, and fixed with tape; (4) Pour the EPDM / phenolic adhesive mixture obtained in step (1) into the groove, cover it immediately after it is full, and start recording the resistance value readings every 30 seconds for a total of 20 minutes, and calculate the resistance change rate X and T max .

[0035] Example 3 obtained T max The interface compatibility rating table in Table 1 is 11 minutes. The EPDM / phenolic erosion-resistant thermal insulation material is prepared by using ammonia-modified phenolic resin and a 2:1 ratio of EPDM / phenolic aldehyde mixed glue with a mass fraction of 20%. The interface compatibility rating is medium. Compared with Example 1, the ratio of EPDM is increased, T max The interface compatibility becomes worse.

[0036] Example 4 The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention comprises the following steps: (1) Dissolve 150 g of EPDM rubber in 700 g of xylene to obtain EPDM glue solution, then add 150 g of ammonia-modified phenolic resin and stir thoroughly at a stirring temperature of 25 °C, a rotation speed of 600 rpm, and a stirring time of 30 min to obtain an EPDM / phenolic mixed glue solution with a mass fraction of 30%; (2) The carbon fiber braid is made into a strip with a length of 12 cm, a width of 2 cm, and a thickness of 0.5 cm. Conductive copper sheets are pasted at both ends along the length direction and connected to a high-precision multimeter. (3) The carbon fiber braid in step (2) is placed in the center of the groove of the special polytetrafluoroethylene rectangular parallelepiped, with both ends of the carbon fiber braid extending out of the groove, and fixed with tape; (4) Pour the EPDM / phenolic adhesive mixture obtained in step (1) into the groove, cover it immediately after it is full, and start recording the resistance value readings every 30 seconds for a total of 20 minutes, and calculate the resistance change rate X and T max .

[0037] Example 4 obtained T max The interface compatibility rating table in Table 1 is 8 minutes. The EPDM / phenolic erosion resistant thermal insulation material is prepared by using ammonia-modified phenolic resin and a 1:1 ratio of EPDM / phenolic aldehyde mixed glue with a mass fraction of 30%. The interface compatibility rating is good. Compared with Example 1, the mass fraction of the EPDM / phenolic aldehyde mixed glue increases, T max increases, and the interface compatibility decreases.

[0038] Example 5 The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention comprises the following steps: (1) Dissolve 200 g of EPDM rubber in 600 g of xylene to obtain EPDM glue solution, then add 200 g of ammonia-modified phenolic resin and stir thoroughly at a stirring temperature of 25 °C, a rotation speed of 600 rpm, and a stirring time of 30 min to obtain an EPDM / phenolic mixed glue solution with a mass fraction of 40%; (2) The carbon fiber braid is made into a strip with a length of 12 cm, a width of 2 cm, and a thickness of 0.5 cm. Conductive copper sheets are pasted at both ends along the length direction and connected to a high-precision multimeter. (3) The carbon fiber braid in step (2) is placed in the center of the groove of the special polytetrafluoroethylene rectangular parallelepiped, with both ends of the carbon fiber braid extending out of the groove, and fixed with tape; (4) Pour the EPDM / phenolic adhesive mixture obtained in step (1) into the groove, cover it immediately after it is full, and start recording the resistance value readings every 30 seconds for a total of 20 minutes, and calculate the resistance change rate X and T max .

[0039] Example 5 T max The interface compatibility rating is 18 minutes. According to the interface compatibility rating table in Table 1, ammonia-modified phenolic resin and 1:1 ratio of EPDM / phenolic resin are used to prepare EPDM / phenolic erosion-resistant insulation materials with a mass fraction of 40%. The interface compatibility rating is poor. Compared with Example 4, the mass fraction of EPDM / phenolic resin mixed glue is further increased, T max The interfacial compatibility decreases rapidly.

[0040] Example 6 The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention comprises the following steps: (1) Dissolve 150 g of EPDM rubber in 700 g of xylene to obtain EPDM glue solution, then add 150 g of boron-modified phenolic resin and stir thoroughly at a stirring temperature of 25 °C, a rotation speed of 600 rpm, and a stirring time of 30 min to obtain an EPDM / phenolic mixed glue solution with a mass fraction of 30%; (2) The carbon fiber braid is made into a strip with a length of 12 cm, a width of 2 cm, and a thickness of 0.5 cm. Conductive copper sheets are pasted at both ends along the length direction and connected to a high-precision multimeter. (3) The carbon fiber braid in step (2) is placed in the center of the groove of the special polytetrafluoroethylene rectangular parallelepiped, with both ends of the carbon fiber braid extending out of the groove, and fixed with tape; (4) Pour the EPDM / phenolic adhesive mixture obtained in step (1) into the groove, cover it immediately after it is full, and start recording the resistance value readings every 30 seconds for a total of 20 minutes, and calculate the resistance change rate X and T max .

[0041] In Example 6, the resistance change rate X continued to increase after 20 minutes, so T max More than 20min, according to the interface compatibility rating table in Table 1, the EPDM / phenolic erosion-resistant insulation material is prepared by using a 30% EPDM / phenolic mixed glue solution with a ratio of 1:1 and boron-modified phenolic resin, and the interface compatibility rating is extremely poor. Combined with the results of Example 4, the process matching of Example 6 using boron-modified phenolic resin to prepare EPDM / phenolic erosion-resistant insulation material is poor.

[0042] The method for characterizing the interface compatibility of EPDM / phenolic erosion-resistant thermal insulation materials of the present invention has a simple and rapid testing process, strong operability, high reliability of results, and has significant advantages.

[0043] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for characterizing the interfacial compatibility of EPDM / phenolic erosion-resistant thermal insulation materials, characterized in that: The following steps are involved: S1, dissolving EPDM rubber with a solvent, adding phenolic resin and mixing well to prepare EPDM / phenolic mixed glue; S2, connecting the two ends of the carbon fiber braid to an ohmmeter with wires to form a loop, then placing the carbon fiber braid in a container, and adding the glue prepared in S1 to the container, so that the carbon fiber braid except the wiring part is immersed in the glue; S3, after pouring the glue, start to record the resistance value reading regularly, the initial resistance value is R0, and the later resistance value is recorded as R i (i=1,2,…,), calculate the resistance change rate X, X=R0 / R i ×100%; the moment when X reaches the maximum is recorded as T max , T max The smaller it is, the better the interface compatibility is.

2. The characterization method according to claim 1, characterized in that: The EPDM rubber in S1 contains, in addition to the EPDM base rubber, one or more of a vulcanizing agent, a vulcanization accelerator, an antioxidant, a flame retardant and a plasticizer.

3. The characterization method according to claim 1, characterized in that: The solvent is one or more of toluene, xylene, cyclohexane, heptane, gasoline, acetone, ethyl acetate, anhydrous ethanol, anhydrous methanol, and ethylene glycol.

4. The characterization method according to claim 1, characterized in that: The phenolic resin is one or more of an ammonia-modified phenolic resin, a sodium-modified phenolic resin, a boron-modified phenolic resin and a barium-modified phenolic resin.

5. The characterization method according to claim 1, characterized in that: When the phenolic resin is mixed, the temperature is 0~60°C, the rotation speed is 500~1000rpm, and the stirring time is 10~60min.

6. The characterization method according to claim 1, characterized in that: The mass fraction of EPDM / phenolic resin mixed glue is 10~50%; the mass ratio of EPDM glue to phenolic resin is 0.5~2:

1.

7. The characterization method according to claim 1, characterized in that: The length of the container is shorter than the length of the carbon fiber braid, and the width and depth are respectively larger than the width and thickness of the carbon fiber braid; the material of the container is one or more of polytetrafluoroethylene, polyvinyl chloride, polymethyl methacrylate and polypropylene; the accuracy of the resistance meter is milliohm level or above.

8. The characterization method according to any one of claims 1 to 7, characterized in that: During the test in S3, the resistance value reading is recorded every 30 seconds.

9. The characterization method according to any one of claims 1 to 7, characterized in that: T max When ≤5min, the interface compatibility is excellent; 5<T max When ≤10min, the interface compatibility is good; 10<T max When ≤15min, the interface compatibility is medium; 15<T max When ≤20min, the interface compatibility is poor; T max When the time is greater than 20 min, the interfacial compatibility is extremely poor.

10. Application of the characterization method according to any one of claims 1 to 9 in the research and development and production quality control of EPDM / phenolic erosion-resistant insulation materials.